MANIFESTATION OF THE STATUES OF DEITIES IN THE LI TIE GUAI TEMPLE IN WEST JAKARTA: A LIFE COURSE PERSPECTIVE - Zaqi, Muhammad; Marwoto, Irmawati (UI Scholars Hub, 2023)
This article discusses the embodiment of the statues of the gods and goddesses at the Li Tie Guai Temple in West Jakarta. The embodiment of the statues in this temple is discussed using a life course perspective. The data used are all the statues of the gods in the temple, totaling thirty statues. The method used is study of literature and field data, followed by data processing which is done by classifying the statues into age, adult, teenager, and children as well as the shape of men, women, and others. The next stage is data interpretation. The results showed that there were more statues depicted in the forms of adults and old people compared to the forms of teenagers and children. This shows that from a life course perspective, a person during his or her lifetime becomes a god more when he or she is mature and old because the process of becoming a god requires special abilities and a purified soul that can be acquired over a long time. Then the embodiment of male statues is more numerous than the embodiment of female statues and others. This shows that in the past, especially in China, men had greater domination than women and others.